2017
DOI: 10.1037/rel0000086
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative religious/spiritual coping and combat exposure as predictors of posttraumatic stress and perceived growth in Iraq and Afghanistan veterans.

Abstract: We examined religious/spiritual (RS) coping from the Survey of Experiences of Returning Veterans (SERV) Study, 630 participants who reported on their demographics, combat exposure, use of positive and negative RS coping, posttraumatic stress disorder (PTSD) symptoms and perceived posttraumatic growth (PPTG). PTSD symptoms and PPTG were inversely correlated. As hypothesized, negative RS coping was inversely associated with PPTG and positively with PTSD, while positive RS coping was related only to PPTG. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 44 publications
5
51
0
Order By: Relevance
“…Thomas and Savoy () showed that the association between trauma exposure and PTG was stronger in people with lower levels of negative religious coping. Positive associations were also found in Park et al, . However, Ahrens et al () and Gerber et al () found no significant links.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…Thomas and Savoy () showed that the association between trauma exposure and PTG was stronger in people with lower levels of negative religious coping. Positive associations were also found in Park et al, . However, Ahrens et al () and Gerber et al () found no significant links.…”
Section: Resultsmentioning
confidence: 67%
“…Consistent pattern of associations was found in the case of negative religious coping and symptoms of disorders: depression (Ahrens et al, ; Henslee et al, ; Leaman & Gee, ), PTSD (Berzengi, Berzenji, Kadim, Mustafa, & Jobson, ; Cuevas et al, ; Currier et al, ; Gerber et al, ; Harris et al, ; Leaman & Gee, ; McCann & Webb, ; Park et al, ; Raines et al, ; Wortmann et al, ; Zukerman, Korn, & Fostick, —only in women; Zukerman, Korn, Shapiro, & Fostick, , avoidance symptoms), distress (Chan & Rhodes, ), suicidal ideations (Currier, Smith, & Kuhlman, ; Kopacz et al, ; Raines et al, ), and substance use (Raines et al, ). Lack of significant associations between the negative coping and symptoms of PTSD was demonstrated in Ahrens et al (), Al‐Hadethe et al (), and Chan and Rhodes ().…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…All but three19 33 46 of these papers reported Cronbach’s alphas for their samples on the PTGI, in order to assess the internal reliability of the scale. All values were excellent, with ranges between 0.9042 and 0.96 21 37. None of the studies employing the PTGI reported on the validity or reliability of the scale within their sample.…”
Section: Resultsmentioning
confidence: 92%